Identification and pathogenicity analysis of a novel non‐tuberculous mycobacterium clinical isolate with nine‐antibiotic resistance. (22nd March 2012) - Zhang, Z.‐Y.; Sun, Z.‐Q.; Wang, Z.‐L.; Hu, H.‐R.; Wen, Z.‐L.; Song, Y.‐Z.; Zhao, J.‐W.; Wang, H.‐H.; Guo, X.‐K.; Zhang, S.‐L.
Abstract With mycobacteriosis increasing, the study of non‐tuberculous mycobacteria is imperative for clinical therapy and management. Non‐tuberculous mycobacteria are naturally resistant to most anti‐tuberculosis drugs. Accordingly, it is important to decipher the biology of the novel non‐tuberculous mycobacteria through complete genomic analysis of novel pathogenic mycobacteria. We describe Mycobacterium sinense JDM601, a novel, slow‐growing mycobacterium of the Mycobacterium terrae complex resistant to nine antibiotics, by clinical presentation, cultural and biochemical characteristics, minimal inhibitory concentrations, and genome‐sequencing analysis. JDM601 is closest to Mycobacterium nonchromogenicum according to mycolic acid composition, but closest to Mycobacterium algericum sp. nov according to 16S rDNA. JDM601 is resistant to isoniazid, streptomycin, rifampin, euteropas, protionamide, capromycin, ciprofloxacin, amikacin and levofloxacin but not ethambutol. The clinical information, mycolic acid composition, and virulence genes indicate that JDM601 is an opportunistic pathogen.